Three new species of Tubifera from Tasmania and New South Wales - Lloyd, Sarah J.; Leontyev, Dmitry V.; Dagamac, Nikki Heherson A. (Phytotaxa, 2019)
Three new myxomycete species, Tubifera glareata, T. tomentosa and T. vanderheuliae, are described on the basis of morphological investigations and the partial 18S rDNA barcoding. Tubifera vanderheuliae, collected in Tasmania and New South Wales, is characterized by small, bouquet-shaped pseudoaethalia, cylindrical sporothecae somewhat extended at the top, and the largest spores known thus far within the genus (7.5–10.5 μm). Tubifera glareata, found thus far only in Tasmania, is somewhat similar to T. applanata found in the Holarctic region, but differs from the latter by the larger spores, absence of ring-like ornamentation on the peridium, and the smaller subspherical pseudoaethalia. Tubifera tomentosa, also collected in Tasmania, differs from the related species T. dudkae by the conspicuous amorphous felt-like cover on the surface of the pseudoaethalia.